Six-Sigma Methodology for Quality Monitoring in a Teaching Hospital Biochemistry Laboratory in Nepal - Mishra, Akash; Pokhrel, Rakesh; Budhathoki, Uttam; Yadav, Binod K; Sharma, Vijay K; Tuladhar, Eans T; Bhattarai, Aseem; Raut, Mithileshwor (Journal of Institute of Medicine Nepal, 2021)
Introduction: Six-sigma is emerging method of choice for performance testing of clinical laboratory. This study was designed to evaluate the performance of 12 routine biochemical analytes on sigma-scale and calculate the quality goal index (QGI). Methods: A cross-sectional study was conducted at Tribhuvan University Teaching Hospital (TUTH), Biochemistry Laboratory for 3 months. BT1500 and BT3500 automated biochemistry analyzers were used. Internal quality control (IQC) performed routinely for 12 clinical analytes for both control levels were recorded from both analyzers and used for calculation of coefficient of variation (CV%). Bias was estimated based on the average difference obtained for each analyte from the target values provided. Values for total allowable errors (TEa) were taken from Clinical Laboratories Improvement Act guidelines. Variables used for calculation of sigma values and QGI were CV%, percentage bias and TEa. Results: Both levels of control for alanine-aminotransferase (ALT) in BT1500 and only control level L2 for aspartate-aminotransferase (AST) in both analyzers showed the sigma value greater than six. Sigma-values between three and six were found for uric acid for both levels of control in both analyzers. Less than three sigma values were obtained for parameters urea, creatinine, albumin, triglyceride, total-cholesterol, alkaline phosphatase (ALP) and magnesium for both levels of control in both analyzers indicating the need towards improvement in these methods. Conclusion: The quality of test for urea, creatinine, albumin, triglyceride, total-cholesterol, ALP and magnesium were unacceptable. Hence, appropriate actions should be taken towards measurement method in these parameters to improve accuracy and report quality.